The Development of News Text-Based Problems Teaching Materials in 12th Grade Students of Vocational High School at TR Sinar Husni of 2019/2020 - Bobby Pratama Putra; Khairil Ansari; Isda Pramuniati (BIRCU, 2020)
This research aims to develop the material teaching of News text based Problem in 12th grade Students of Vocational High School at TR Sinar Husni. The methods used is quantitative method. It also use random sampling system. The product that was developed was in the form of a problem-based module on writing news text material entitled